1987
DOI: 10.1007/bf03014345
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high-dose mannitol on serum and urine electrolytes and osmolality in neurosurgical patients

Abstract: The effect of mannitol on serum and urine electrolytes and osmolali~_ was investigated intraoperatively in neurosurgical patients. Patients in Group A (n = 7) received 1 gm,kg -t of 20 per cent mannitol ("low"-dose) Osmotic diuretics are used to reduce intracranial pressure and decrease brain bulk in neurosurgical patients, t'2 lntraoperatively, mannitol is most frequently administered in dose ranges of 0.25-1 gm.kg -I. More recently, high-dose mannitol (2 gm'kg -~) has been shown to have a protective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 14 publications
6
36
1
2
Order By: Relevance
“…Hyperosmolar therapy using mannitol or hyperosmolar saline is a key intervention to overcome cerebral edema. Due to potential complications of mannitol such as intravascular volume depletion, hypotension, and hyperkalemia, hypertonic saline has been increasingly used as a safer alternative to mannitol (11,17,18). However, even though it has safety advantages over mannitol, there is a still controversy on the optimal dose or concentration of hypertonic saline.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperosmolar therapy using mannitol or hyperosmolar saline is a key intervention to overcome cerebral edema. Due to potential complications of mannitol such as intravascular volume depletion, hypotension, and hyperkalemia, hypertonic saline has been increasingly used as a safer alternative to mannitol (11,17,18). However, even though it has safety advantages over mannitol, there is a still controversy on the optimal dose or concentration of hypertonic saline.…”
Section: Discussionmentioning
confidence: 99%
“…At the lower end of this range, such an increase would be insufficient (10 mM (Cloyd et al, 1986;Rudehill et al, 1993) ) or perhaps barely sufficient (18 mM (Cloyd et al, 1986)) to afford delay of AD. In the upper end, a 32 mM increase (Manninen et al, 1987) would probably be somehow effective in delaying AD. In fact, we showed that in vitro the addition of 25 mM mannitol (increasing osmolarity by 25 mOsm) significantly delays AD.…”
Section: Discussionmentioning
confidence: 99%
“…Such a dose leads, still in human patients, to a maximum increase in serum osmolarity of about 10-32 mOsm (Cloyd et al, 1986;Manninen et al, 1987;Rudehill et al, 1993). When experimental animals are considered, administration of 1 g/Kg body weight to rats yelded a serum osmolarity increase of 4 mOsm (Thenuwara et al, 2002).…”
Section: Literature Search On Serum Osmolarity Changes In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the presence of a disrupted BBB, an osmotic gradient is still established and mannitol is still able to reduce total brain volume (12,13). Hypertonic mannitol solutions rapidly draw water into the extracellular compartment increasing plasma volume (2), which transiently dilutes extracellular sodium (14)(15)(16). In the kidney, mannitol acts as an osmotic diuretic resulting in the excretion of large volumes of free water (2,17).…”
Section: Introductionmentioning
confidence: 99%